MODERN APPROACHES TO THE TREATMENT OF LARYNGEAL CANCER - Suleymanov D.A; Toraev T.D; Karimov O.M; Tajibaev D.R; Yigataliev A.B. (Western European Studies, 2024)
laryngeal cancer is a malignant tumor disease of this member, which is often associated with smoking cigarettes, heavy alcohol consumption and other factors. In recent years, new and effective methods have appeared in medicine for the treatment of hiccups. This article focuses on the analysis of the results of several scientific studies dedicated to the study of modern methods of treatment, their effectiveness
Keywords: laryngeal cancer; modern treatments; surgical procedure; radiotherapy